Analysis of Pseudomonas sp. polycyclic aromatic hydrocarbons degradation proteins by LC-MS/MS - Adenan, Suzana; Chee, Fah Wong; Syed Abdul Azziz, Saripah Salbiah; Si Nang, Som Cit; Misnan, Rosmilah; Lamasudin, Dhilia Udie; Yii, Benjamin Chung Lau (Universiti Putra Malaysia Press, 2022)
The uncontrolled release of Polycyclic Aromatic Hydrocarbons (PAHs) had warned of some environmental issues. A bioremediation method by introducing PAHs-degraders bacteria into the contaminated area had issued with a few limitations including survival of strains and against international legislation which we believed that the problems can be reduced with biocatalysis remediation strategies. Biocatalysis of PAHs was detected from biostimulated-PAHs degrading enzymes (PDEs) from Pseudomonas putida strain B4 (PPB4) (Figure 1). Extracellular PDEs were determined by production of 9,10 anthraquinone from PAH biodegradation assay. 2DE analysis was done to compare the expression level of biostimulated and non-stimulated protein. A spot was detected as an upregulated protein while 3 spots were found to be downregulated proteins. These spots undergo LC-MS analysis for protein identification purposes utilizing SEQUEST HT software against the most recent Uniprot database. The results revealed that the upregulated proteins are chaperonin protein (WP_010952474.1), ATP synthase subunit beta (WP_003253197.1) and two dehydrogenase proteins, which are dihydrolipoyl dehydrogenase (WP_010954949.1) and malate dehydrogenase (WP_004575488.1). While downregulated proteins were identified as azurin (WP_003249580.1) and cold-shock protein (WP_003250656.1). In future, these proteins will be further expressed and tested for their ability to work together to achieve the best enzymes consortium for biocatalysis remediation.